The Steady-State Serum Concentration of Genistein Aglycone Is Affected by Formulation: A Bioequivalence Study of Bone Products. (31st December 2012) - Bitto, Alessandra; Burnett, Bruce P.; Polito, Francesca; Russo, Silvia; D'Anna, Rosario; Pillai, Lakshmi; Squadrito, Francesco; Altavilla, Domenica; Levy, Robert M.
Abstract : An FDA-regulated, prescription medical food (Fosteum; 27 mg natural genistein, 200 IU cholecalciferol, 20 mg citrated zinc bisglycinate (4 mg elemental zinc) per capsule) and an over-the-counter (OTC) supplement (Citracal Plus Bone Density Builder; 27 mg synthetic genistein, 600 mg elemental calcium (calcium citrate), 400 IU vitamin D3, 50 mg magnesium, 7.5 mg zinc, 1 mg copper, 75 μ g molybdenum, 250 μ g boron per two tablets) were compared to a clinically proven bone formulation (27 mg natural genistein, 400 IU cholecalciferol, 500 mg elemental calcium (calcium carbonate) per tablet; the Squadrito formulation) in an 8-day steady-state pharmacokinetic (PK) study of healthy postmenopausal women (n = 30 ) randomized to receive 54 mg of genistein per day. Trough serum samples were obtained before the final dose on the morning of the ninth day followed by sampling at 1, 2, 4, 6, 8, 10, 12, 24, 36, 48, 72, and 96 hrs. Total serum genistein, after β -glucuronidase/sulfatase digestion, was measured by time-resolved fluorometric assay. Maximal time (T max ), concentration (C max ), half-life (T 1 / 2 ), and area under the curve (AUC) were determined for genistein in each formulation. Fosteum and the Squadrito study formulation were equivalent for genistein T max (2 hrs), C max (0.7 μ M), T 1 / 2 (18 ± 6.9 versus 21 ± 4.9 hrs), and AUC (9221 ± 413 versus 9818 ± 1370 ng·hr/mL). The OTC supplement's synthetically derived genistein, however, showed altered T max (6 hrs), C max (0.57 μ M), T 1 / 2 (8.3 ± 1.9 hrs), and AUC (6474 ± 287 ng·hr/mL). Differences in uptake may be due to multiple ingredients in the OTC supplement which interfere with genistein absorption.